Pertrochanteric fracture of the femur in the Finnish National Hospital Discharge Register: validity of procedural coding, external cause for injury and diagnosis - Huttunen, Tuomas T (BioMed Central, 2014)
BACKGROUND: Hospital discharge data is routinely collected in Finland and it is an invaluable source of information when assessing injury epidemiology as well as treatment. The database can be used when planning injury prevention and redirecting resources of the health care system. Most recently our hospital discharge register has been used to assess the incidence of surgical treatment of common fractures. This study was aimed to evaluate the coverage and accuracy of the Finnish National Hospital Discharge Register (NHDR) focusing on hip fractures. In other words, patients hospitalized for a pertrochanteric hip fracture were used to assess the validity of the NHDR. METHODS: The validity of the NHDR was assessed by comparing the data in hospital discharge register with the original patient records and radiographs in three separate hospitals; Tampere University Hospital, Hatanpää City Hospital of Tampere, and the Central Hospital of Kanta-Häme. The study analysis included 741 patients hospitalized due to pertrochanteric hip fracture between 1(st) January 2008 and 31(st) December 2010. RESULTS: The diagnosis was correctly placed on 96% (95% CI: 94 to 97%) of the 741 patients when radiographs were used as golden standard. The procedural coding had coverage of 98% (95% CI: 96 to 98%) and an accuracy of 88% (95% CI: 85 to 90%). The coverage of the external cause for injury was found to be 95% (95% CI: 94 to 97%) with an accuracy of 90% (95% CI: 87 to 92%). CONCLUSIONS: Our results show that the validity of the Finnish NHDR is excellent as determined by accuracy of diagnosis and both accuracy and coverage of procedural coding and external cause for injury. The database can be used to assess injury epidemiology and changes in surgical treatment protocols.